THE EFFECT OF PRODUCT PLACEMENT ON "IKATAN CINTA" DRAMA ON PURCHASE INTENTION OF "LEMONILO" NOODLES - Chumairoh, Chumairoh; Pananingrum, Erminati (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2023)
This study aims to determine and explain the effect of product placement on the purchase intention of Lemonilo noodle products moderated by consumer attitudes in the "Ikatan Cinta" drama. This study uses a quantitative approach. The research method used is verification, with explanatory research that aims to test hypotheses to explain the position between variables. The variables studied were product placement, consumer attitudes, and purchase intentions. Respondents were used as many as 100 people distributing questionnaires to people who had watched the "Ikatan Cinta" drama and knew product placement in the "Ikatan Cinta" drama. The test tool uses Moderated Regression Analysis (MRA) on the SPSS tool. Based on the analysis, it can be concluded that product placement influences purchase intention, and attitude does not moderate the relationship between product placement and purchase intention. The test results for the coefficient of determination show that the level of product placement contribution and attitude towards purchase Intention is 52.5%, and the remaining 47.5% is influenced by other factors not examined in this study.